1)c3h6+hoh(н+) =c3h7oh-получение
2c3h7oh+2na=2c3h7ona+h2
ch3-ch2-ch2oh+cuo(t) =ch3-ch2-coh+cu+h2o
2)сh3-ch2-ch2-ch2oh + cuo(t) =ch3-ch2-ch2-coh +cu+h2o-получение
ch3-ch2-ch2-coh+h2=ch3-ch2-ch2-ch2oh
ch3-ch2-ch2-coh+ag2o(t) = ch3-ch2-ch2-cooh+2ag
3)2ch3-(ch2)3-cooh+2na=2ch3-(ch2)3-coona+h2
2ch3-(ch2)3-cooh+mgo=(ch3-ch2-ch2-ch2-coo)2mg+h2o
ch3-(ch2)3-cooh+naoh=ch3-(ch2)3-coona+h2o
2ch3-(ch2)3-cooh+na2co3=2ch3-(ch2)3-coona+co2+h2o
4)c2h5oh+ch3-cooh= c2h5-o-co-ch3+h2o
c5h11oh+h-cooh= c5h11-o-co-h +h2o
c7h13oh+c2h5-cooh= c7h13-o-co-c2h5+h2o
c5h11oh+ c5h11-cooh=c5h11-o-co-c5h11+ h2o
Нужно воспользоваться формулой разности квадратов практически во всех примерах: (a - b)(a + b) = a² - b².
Выполните умножение:
1) 5b(b - 1)(b + 1) = 5b(b² - 1) = 5b³ - 5b;
2) (c + 2)(c - 2) · 8c² = (c² - 4) · 8c² = 8c⁴ - 32c²;
3) (m - 10)(m² + 100)(m + 10) = (m - 10)(m + 10)(m² + 100) =
= (m² - 100)(m² + 100) = m⁴ - 10 000;
4) (a² + 1)(a² - 1)(a⁴ + 1) = (a⁴ - 1)(a⁴ + 1) = a⁸ - 1;
Упростите выражение:
1) (x + 1)(x - 1) - (x + 5)(x - 5) + (x + 1)(x - 5) = x² - 1 - (x² - 25) + x² - 5x + x - 5 = x² - 1 - x² + 25 + x² - 4x - 5 = x² - 4x + 19;
2) 81a⁸ - (3a² - b³)(9a⁴ + b⁶)(3a² + b³) = 81a⁸ - (3a² - b³)(3a² + b³)(9a⁴ + b⁶) = 81a⁸ - (9a⁴ - b⁶)(9a⁴ + b⁶) = 81a⁸ - (81a⁸ - b¹²) = 81a⁸ - 81a⁸ + b¹² = b¹².